Accounting and finance in UK universities: Academic labour, shortages and strategies. Issue 6 (November 2018) - Smith, Sarah Jane; Urquhart, Vivien
Abstract: This paper contributes to the literature on change in the higher education sector arising from massification, increased political control, international mobility and competition. Drawing on various data sources and labour shortage models, it considers academic labour in UK accounting and finance academia over the period 2000 to 2012. A disequilibrium between supply and demand is evidenced through the identification of recruitment problems, unfilled vacancies, and retirements. The impact of research assessment on faculty backgrounds is shown to result in inadequate supply of faculty with the required skills. Strategic responses to labour shortages include: increased recruitment efforts, early promotions, enhanced remuneration and reducing restrictions on occupational entry. The consequences and future implications of shortages and strategies are considered. In particular, the decoupling of research and teaching in accounting is challenging the future existence of accounting as an academic discipline. The current generation of accounting academics is also under threat – if they neither excel at research nor are professionally-qualified they risk becoming undesirable.